2011
DOI: 10.1111/j.1740-8261.2011.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and Pancreaticobiliary Mri and MR Cholangiopancreatography With and Without Secretin Stimulation in Normal Cats

Abstract: Magnetic resonance (MR) cholangiopancreatography is useful in humans to diagnose biliary and pancreatic diseases. Some of these protocols incorporate the use of secretin, which stimulates the exocrine pancreas to release bicarbonate with secondary dilation of the pancreatic duct. We compared the utility and quality of multiple hepatic-pancreaticobiliary MR imaging sequences before and after secretin stimulation of the pancreatic duct in five healthy cats. Multiple MR sequences were evaluated, including fast Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…25,26,37,38 All cats in this study had more pronounced dilation of the pancreatic duct post-secretin stimulation compared with previously studied normal cats. 25,26 It has been suggested that mild dilation post-secretin could indicate retention of ductal elasticity. 37 In contrast, the two cats with pancreatic cysts and the most severe pancreatic duct dilation did not respond to secretin stimulation, suggesting minimal duct elasticity.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…25,26,37,38 All cats in this study had more pronounced dilation of the pancreatic duct post-secretin stimulation compared with previously studied normal cats. 25,26 It has been suggested that mild dilation post-secretin could indicate retention of ductal elasticity. 37 In contrast, the two cats with pancreatic cysts and the most severe pancreatic duct dilation did not respond to secretin stimulation, suggesting minimal duct elasticity.…”
Section: Discussionmentioning
confidence: 54%
“…Two of five normal cats had gall bladder debris which had similar imaging characteristics. 26 Nine of 10 cats had a mildly thickened and moderately enhancing gall bladder wall [mean 2.2 mm ± 0.3 mm (median 1.9 mm)] (Figure 5b). In normal cats, the gall bladder wall was mildly contrast enhancing and was difficult to measure with electronic calipers owing to its small size, which required magnifying the image until pixelated [1.7 mm-0.5 mm (median 1.2 mm)].…”
Section: Ultrasound Imaging Resultsmentioning
confidence: 99%
See 3 more Smart Citations